Effectiveness and safety of tenofovir disoproxil fumarate in chronic hepatitis B: a 3-year prospective field practice study in Germany - Petersen, Jörg; Eisenbach, Christoph (Digestive diseases and sciences, 2016)
Background and AimsMultiple clinical trials have demonstrated the efficacy and safety of tenofovir disoproxil fumarate (TDF) in chronic hepatitis B (CHB). However, long-term efficacy and safety data for TDF in real-life clinical practice are limited.MethodsProspective German field practice study in CHB-mono-infected patients. Patients were TDF-naïve but could have been treated previously with other HBV antivirals.ResultsEfficacy analysis included 400 patients; 301 (75 %) completed 36 months of TDF treatment. Both treatment-naïve and treatment-experienced patients showed a rapid decline in HBV DNA within 3 months of TDF initiation. After 36 months, HBV DNA < 69 IU/mL was achieved by 91 % of treatment-naïve patients (90 and 92 % in hepatitis B “e” antigen [HBeAg]-positive and [HBeAg]-negative, respectively) and 96 % of treatment-experienced patients (93 and 97 %, respectively). Three patients experienced virologic breakthrough, all with reported non-compliance. Overall, 5.7 % HBeAg-positive and 2.2 % HBeAg-negative patients lost hepatitis B surface antigen. Safety data were consistent with the known TDF safety profile; the most commonly reported adverse events possibly related to TDF were fatigue (2.0 %) and headache (2.0 %). Few patients (1.3 %) experienced renal-related adverse reactions. Creatinine clearance remained relatively stable over time; patients responded favorably where TDF was dose adjusted per label for decreased creatinine clearance.ConclusionsTDF showed a favorable tolerability profile and induced rapid and sustained suppression of HBV DNA in patients with CHB treated for up to 3 years in routine clinical practice, irrespective of treatment history. Efficacy and safety in this heterogeneous patient population were consistent with data from clinical trials.